2009
DOI: 10.2114/jpa2.28.115
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Balance, Falls, and Bone Mineral Density of a Home-based Exercise Program without Home Visits in Community-Dwelling Elderly Women: a Randomized Controlled Trial

Abstract: The aim of the present study was to investigate the effects of home-based exercise without home visits on physical function, falls, and bone mineral density in community-dwelling elderly women. Sixty community-dwelling, elderly (> or =65 years of age) women were recruited from a Japanese community. Subjects were randomly assigned to a home-based exercise group or a control group. The subjects assigned to the home-based exercise group performed home-based exercise without home visits 3 times per week for 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 36 publications
(42 reference statements)
0
59
0
2
Order By: Relevance
“…Improvements in balance self-efficacy in women with osteoporosis have been reported after group-based exercise programs in the form of resistance training, weight-bearing exercises, tai chi, and task-oriented training programs [30,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in balance self-efficacy in women with osteoporosis have been reported after group-based exercise programs in the form of resistance training, weight-bearing exercises, tai chi, and task-oriented training programs [30,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Where effects were non-significant, some instances of trends towards reductions in falls rates were observed [52,63]. In other cases, additional factors such as exercise type and intensity may have been influential [29,32,42].…”
Section: Frequencymentioning
confidence: 99%
“…On the contrary, no significant improvement in femoral neck and lumbar spine BMD after 12 months of home-based strength training combined with aerobic training and stretching in elderly women with symptomatic osteoporosisrelated vertebral fractures (32).Similarly, strength training for lower limb in concert with balance and impact trainings in community-dwelling elderly women had no significant effect on bone mineral density (28). Plus, 30-months supervised home-based impact trainings resulted in non-significant impact on BMD.…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…Substantial number of studies have shown dramatic improvements in strength (22,24,25,33,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), balance (33,35,41,43,47), mobility (40,46), agility (43,47), flexibility (47), endurance (43), cardiovascular fitness (37,47), quality of life (32,36,40,49), and physical abilities (28,35,37,39,(44)(45)(46)(48)(49)(50) with various home-based resistance training programs.…”
Section: Functional Abilitiesmentioning
confidence: 99%